Pensions for public-sector employees : lessons from OECD countries’ experience - Whitehouse, Edward (Washington, DC, 2016)
"In 27 out of 34 OECD member countries, there is institutionally separate retirement-income provision for some or all public-sector workers. But the scope of these pension schemes varies significantly: from a modest top-up to the national pension arrangements (covering private-sector workers as well) to entirely independent retirement-income regimes. Average expenditure on these schemes amounts to about 1.5 percent of GDP, or nearly a quarter of total public pension spending. Public-sector pension reform is an issue of great political importance in many countries. Central governments’ workforces are ageing rapidly in all but four of the 26 countries for which data are available. One in three of central-government employees were aged 50 and over in 2009, compared with 22 percent in 1995. This rapid ageing is pushing up the cost of pension schemes at a time when many OECD countries are embarking on fiscal consolidation. This paper examines the arguments and the options for reforming public-sector pension schemes from an international viewpoint. It assesses five different policies to reduce expenditures or increase contribution revenues, showing how these can have very different effects in a public-sector scheme than with national retirement-income arrangements."